Functional Outcome of CAD/CAM-Assisted versus Conventional Microvascular, Fibular Free Flap Reconstruction of the Mandible: A Retrospective Study of 30 Cases - Ritschl, Lucas M.; Mücke, Thomas; Fichter, Andreas; Güll, Florian D.; Schmid, Christopher; Duc, Jean Marc Pho; Kesting, Marco R.; Wolff, Klaus-Dietrich; Loeffelbein, Denys J. (Journal of Reconstructive Microsurgery, 2017)
Background Different advantages of virtually planned and guided mandibular reconstructions have been described. Functional analyses and comparisons with conventionally reconstructed patients.Methods We retrospectively analyzed 30 cases of mandibular reconstructions that involved virtually planned or conventional microvascular, fibular free flaps that occurred between April 2011 and December 2014 at a single center. The results were also compared with a healthy cohort of 30 participants. Axiographic measurements were performed postoperatively, and uni- and multivariate regressions analyses were performed to determine the association between possible predictor variables on functional outcome.Results Operation time, hospital stay, number of osteotomies, incidence of postoperative temporomandibular joint pain, noise, and tension did not differ significantly between the conventional and computer-aided design/computer-aided manufacturing (CAD/CAM) groups (each p > 0.05). Mouth opening and protrusion and laterotrusion also did not differ significantly (each p > 0.05) but were significantly reduced compared with the healthy group. Univariate analysis showed a significant influence of postoperative irradiation on mouth opening and laterotrusion in the conventional group (p = 0.047 and p = 0.028). In addition, multivariate analysis showed a significant influence of indication and number of osteotomies on laterotrusion (p = 0.005 and p = 0.043). Uni and multivariate analyses revealed a significant influence of indication, preoperative irradiation, and number of osteotomies on protrusion and mouth opening in the CAD/CAM group (p = 0.016, p = 0.044, and p = 0.028).Conclusion CAD/CAM-assisted reconstructions of the mandible give comparable functional results with those of the conventional technique, but no functional superiority has been established. Nevertheless, the integration of virtual planning and guided surgery is definitely of significant value but should be indicated individually case by case.
Keywords: fibula free flap; mandibular reconstruction; angiography; functional analysis